U(S)3 Serine/Threonine Protein Kinase from MDV-1, MDV-2, and HVT Differentially Regulate Viral Gene Expression and Replication - Liao, Yifei (Microorganisms, 2021)
Gallid alphaherpesvirus 2 (GaHV-2), commonly known as Marek’s disease virus type 1 (MDV-1), is an oncogenic avian alphaherpesvirus, and along with its close relatives—Gallid alphaherpesvirus 3 (GaHV-3) or MDV-2 and Meleagrid alphaherpesvirus 1 (MeHV-1) or turkey herpesvirus (HVT)—belongs to the Mardivirus genus. We and others previously showed that MDV-1 U(S)3 protein kinase plays an important role in viral replication and pathogenesis, which could be partially compensated by MDV-2 and HVT U(S)3. In this study, we further studied the differential roles of MDV-1, MDV-2 and HVT U(S)3 in regulating viral gene expression and replication. Our results showed that MDV-2 and HVT U(S)3 could differentially compensate MDV-1 U(S)3 regulation of viral gene expression in vitro. MDV-2 and HVT U(S)3 could also partially rescue the replication deficiency of MDV-1 U(S)3 null virus in the spleen and thymus, as determined by immunohistochemistry analysis of MDV-1 pp38 protein. Importantly, using immunohistochemistry and dual immunofluorescence assays, we found that MDV-2 U(S)3, but not HVT U(S)3, fully compensated MDV-1 U(S)3 regulation of MDV-1 replication in bursal B lymphocytes. In conclusion, our study provides the first comparative analysis of U(S)3 from MDV-1, MDV-2 and HVT in regulating viral gene expression in cell culture and MDV-1 replication in lymphocytes.